THE USE OF TOTAL PHYSICAL RESPONSE IN TEACHING IMPERATIVE SENTENCES AT SMP N 6 KOTA TERNATE - Irmawati Kardi; Agus Supriyadi; Fitria Wulan Sari (Jurnal Bilingual, 2023)
The objective of this research is to discuss the effectiveness of the Total Physical Response (TPR) method in teaching imperative sentences for grade 7 students of SMP Negeri 6 Kota Ternate. This research was experimental research. The design of this research used a pre-experiment and the population in this research were students of class 7A SMP N 6 Kota Ternate with a total population of 186 students. Therefore, the researcher used convenience sampling where the authors 30 students as a sample in this research. The instruments used to collect data were pre-test, post-test, and questionnaire. The results of the average pre-test score of 17.66 and the average post-test score of 82.66.Â  In addition, the results of the t-test received are greater than the t-table, where the t-test is 33. 163 and the t-table are significantly 0.05 = 1. 699 with df = 29 so there is a significant development of studentsâ€™ vocabulary (imperative sentence) and the ability to use the Total Physical Response method because it can improve grammar and vocabulary skills, especially imperative sentence.